Development and Validation of a Cardiopulmonary Resuscitation (CPR) Questionnaire for Knowledge, Critical Thinking, and Skills Assessment - Dolly Rani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Cardiopulmonary Resuscitation (CPR) is a critical life-saving skill that requires not only technical competency but also knowledge and critical decision-making. Assessing these competencies through reliable and valid tools is essential for evaluating training outcomes and ensuring preparedness of learners. This study aimed to test the reliability and validity of a newly developed CPR questionnaire consisting of three sections: Knowledge (10 items), Critical Thinking (10 items), and Skill Development (10 items). Data were collected from 60 participants and analyzed using Kuder-Richardson Formula-20 (KR-20) and test-retest method for dichotomous items, Cronbach’s alpha for Likert-type items, item analysis (difficulty and discrimination indices), Kaiser-Meyer-Olkin (KMO) for construct validity, and inter-scale correlations for convergent validity. Results showed high reliability coefficients across all sections (Knowledge KR-20 = 0.945, Knowledge (test-retest method) = 0.97, Critical Thinking KR-20 = 0.925, Critical Thinking (test-retest method) = 0.99, and Skill Development α = 0.967). Item analysis indicated moderate to high difficulty with strong discrimination indices, and no item was flagged for poor performance. The Skill Development scale showed acceptable sampling adequacy (KMO = 0.717) with evidence of strong inter-item correlations. Convergent validity was supported by strong correlations between Knowledge, Critical Thinking, and Skill scales (r = 0.84–0.94). The study concludes that the CPR questionnaire is a highly reliable and valid instrument for measuring CPR competencies. Recommendations include maintaining the items, revising overly easy critical thinking questions, and reducing redundancy in the skill section for efficiency.